IMPACT OF HAVING A CONFIDANT ON DEPRESSION AMONG OLDER WOMEN WHO HAVE EXPERIENCED SPOUSAL PHYSICAL ABUSE. (11th November 2018) - Yoon, S; Cummings, S; Nugent, W
Abstract: Intimate Partner Violence (IPV) is a severe issue for older adults. (Sylaska & Edwards, 2014). IPV in later life is expected to increase as baby boomers age (Roberto, McPherson, & Brossoie, 2013). Women exposed to IPV are at risk of depression in later life (Chuang et al., 2012). Social support may be a crucial protective factor against this susceptibility (Ai, Pappas, & Simonsen, 2015). Having a confidant is associated with better mental health among people with depression (Bookwala, Marshall, & Manning, 2014). This study investigated the influence of having a confidant on depression among older women after spousal/partner physical abuse. Data were drawn from the 2003–2005 wave of the Wisconsin Longitudinal Study. The sample included female respondents reporting a history of physical abuse by a spouse or romantic partner. Multiple regression was employed. The dependent variable, depression symptoms, was measured using the Center for Epidemiologic Studies – Depression Scales (CES-D) (Radloff, 1977), (α =.90). Having a confidant was measured using a binary question, "Is there a friend outside your family with whom you can really share your very private feelings and concerns?" Control variables were health and current marital status. Results show having a confidant(Beta = - .19) negatively influenced depression, F (5, 368) =16.311, p <0.001, R=.43 and Adj. R2 = .17. Findings indicate that women who suffer relationship abuse may reduce depressive symptoms by interacting with reliable confidants. Service providers should promote clients' development of and interactions with trustworthy people within safe environments.